2011
DOI: 10.1016/s2255-4971(15)30179-8
|View full text |Cite
|
Sign up to set email alerts
|

Femoral Anteversion and the Neck-Shaft Angle: Relationship With Hip Osteoarthritis

Abstract: Objective: To compare the existence of agreement between measurements of anteversion of the femoral neck and the degrees of osteoarthritis and abnormality of the neck-shaft angle in patients with unilateral idiopathic hip osteoarthritis, among three evaluators. Methods: Forty-two patients with unilateral hip osteoarthritis were evaluated by means of simple radiography and computed tomography. Results: It was observed that there was no significant variation in femoral anteversion between the diseased and health… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 20 publications
0
14
0
Order By: Relevance
“…It was reported that the femoral neck-shaft angle and femoral anteversion did not have a significant relationship with the development of hip osteoarthritis. 19 Therefore, it is known that the variations in the proximal femur do not have a relationship with arthrosis of the hip joint and that such conditions only cause anatomical changes. Worlicek et al, conducted a study in 2016 and showed that femoral anteversion was not a suitable reference that can be used during surgery on patients who underwent total hip replacement.…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that the femoral neck-shaft angle and femoral anteversion did not have a significant relationship with the development of hip osteoarthritis. 19 Therefore, it is known that the variations in the proximal femur do not have a relationship with arthrosis of the hip joint and that such conditions only cause anatomical changes. Worlicek et al, conducted a study in 2016 and showed that femoral anteversion was not a suitable reference that can be used during surgery on patients who underwent total hip replacement.…”
Section: Discussionmentioning
confidence: 99%
“…Abnormal morphology, such as joint deformity, has been observed to affect the development of early osteoarthritis (e.g. in cases of high neck‐shaft angle [NSA]). Other morphological parameters, such as the femoral head diameter (FHD) and the anteversion angle (ATA), influence the range of motion (ROM) of the hip joint.…”
Section: Introductionmentioning
confidence: 99%
“…They found good inter & intra observer reliability in their methodology. Many western authors also observed good inter observer correlation in measuring NSA [31,32].…”
Section: Resultsmentioning
confidence: 86%